2023
DOI: 10.3390/agronomy13112785
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Growth of Silage Maize by Adjusting Planting Density and Nitrogen Application Rate Based on Farmers’ Conventional Planting Habits

Yinsen Qian,
Quan Ma,
Zhen Ren
et al.

Abstract: Silage maize is cultivated due to its high nutritional value as a forage. China’s recent agricultural policy promotes the popularization and cultivation of silage maize. The production of silage maize is affected by planting density and nitrogen application. Based on investigating the planting habits of local farmers, we adjusted the planting density and nitrogen application rate to optimize the growth of silage maize. This study was conducted to investigate the effects of planting density (65,000 plant ha−1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Our findings indicate that as the planting density was increased from 60,000 to 75,000 plants•hm −2 , the silage maize yield exhibited a consistent increase, albeit without a significant difference between 75,000 and 90,000 plants•hm −2 (Figure 1). Qian et al [22] similarly observed a significant increase in the silage maize yield when the planting density was increased from 65,000 to 80,000 plants•hm −2 , with no significant difference between 80,000 and 95,000 plants•hm −2 . This finding suggests that high planting densities can hamper silage maize growth, compensating for yields per hectare with a higher number of plants exhibiting lower yields per plant [23].…”
Section: Effects Of Nitrogen Application Rate and Planting Density On...mentioning
confidence: 93%
“…Our findings indicate that as the planting density was increased from 60,000 to 75,000 plants•hm −2 , the silage maize yield exhibited a consistent increase, albeit without a significant difference between 75,000 and 90,000 plants•hm −2 (Figure 1). Qian et al [22] similarly observed a significant increase in the silage maize yield when the planting density was increased from 65,000 to 80,000 plants•hm −2 , with no significant difference between 80,000 and 95,000 plants•hm −2 . This finding suggests that high planting densities can hamper silage maize growth, compensating for yields per hectare with a higher number of plants exhibiting lower yields per plant [23].…”
Section: Effects Of Nitrogen Application Rate and Planting Density On...mentioning
confidence: 93%